(3LGeY GdJhGQjN GdeUQjI aj PcQ Gdedhc hGdNdaGA hGdSdGWjf GdESdGejIs - (3MSf Hf EHQGgje Hf MSf Hf eMeO, GdeYQha HGdHjWGQ,J (B1273 (3g` s
(3ChdgG (B:s
(3hHYO agPG JGQjN dWja LeY ef GdcJH GddWGFa LeYJg dMVQI Gdehdi GdCYXe s
(3BNQgG (B:s
(3gPG eGLeYfGg Edi gPG GdeMd hEf jSQ HYO Pdc TF , PjdfG Hg Ef TGA Gddg JYGdi, hMQQ Pdc HeUQ GdeMQhSg ai GdOjhGf GdYGdi Sfg (B679(3g` s
(3fSNI NRGFfjI HQSe NRGfI GdSdWGf bdGhhfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B178 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B194s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B127 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHg GdCgdjg ai HGQjS (B(1543) s
Keywords: (3GdJGQjNs